2011
DOI: 10.1007/s10236-011-0428-1
|View full text |Cite
|
Sign up to set email alerts
|

A model study of tidal distributions in the Celtic and Irish Sea regions determined with finite volume and finite element models

Abstract: An unstructured mesh tidal model of the west coast of Britain, covering the Celtic Sea and Irish Sea is used to compare tidal distributions computed with finite element (F.E.) and finite volume (F.V.) models. Both models cover an identical region, use the same mesh, and have topography and tidal boundary forcing from a finite difference model that can reproduce the tides in the region. By this means solutions from both models can be compared without any bias towards one model or another. Two dimensional calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Since this is underestimated in the FV model, compared with observations, the surge is less damped in the FV model compared with the FE model. This is consistent with earlier tidal calculations in which Davies et al (2010) found that M 2 tidal elevations in the eastern Irish Sea computed with the FV model tended to be about 25 cm less than those computed with the FE model (see Tables 1, 2 and 3).…”
Section: Westerly Wind Stress-induced Surge Elevationssupporting
confidence: 92%
See 4 more Smart Citations
“…Since this is underestimated in the FV model, compared with observations, the surge is less damped in the FV model compared with the FE model. This is consistent with earlier tidal calculations in which Davies et al (2010) found that M 2 tidal elevations in the eastern Irish Sea computed with the FV model tended to be about 25 cm less than those computed with the FE model (see Tables 1, 2 and 3).…”
Section: Westerly Wind Stress-induced Surge Elevationssupporting
confidence: 92%
“…This amplification gives rise to the appreciable differences shown in Table 1. A consequence of these differences in the M 2 solution is that the FV model tends to underpredict the amplitude of the higher harmonics compared with the FE model which is in good agreement with observations (see Davies et al 2010; see Tables 2 and 3).…”
Section: Southerly Wind Solutionsupporting
confidence: 85%
See 3 more Smart Citations